China joins Linux bandwagon. - Goad, G. Pierre; Holland, Lorien (Far Eastern Economic Review, 2000)
Part of a special section on the battle between Microsoft Windows and Linux for control of the Chinese computer operating system market. The popularity of Linux software is increasing in China, and it may help to ease Chinese fears of foreign domination and perceived security risks. The popularity of Linux is the result of a number of factors: The software and the underlying source code are freely available, it can be customized and improved by local software developers, it can be copied and installed on multiple machines for free, and it could offer China the chance to become a player in the world software industry. Chinese and foreign companies are already interested in the opportunities available through Linux, and the Chinese government's and computer industry's interest stems from the security Linux offers, the economic development it could deliver for China, and the chance to retain some national pride—Linux is not owned by anybody.